How the pandemic fuels linguistic change : lexical innovations in L1 and L2 English varieties - Pura, Cielo May; Gustilo, Leah; Biermeier, Thomas (Penerbit Universiti Kebangsaan Malaysia, 2022)
Wars and conquests have always opened the floodgates of new words and meanings into the lexicon of the English language. Another kind of war that opens the floodgates for the passage of neologisms into the English language is the war on health during epidemics or pandemics. The present study utilized the News On the Web (NOW) corpus of English-corpora.org to (1) produce a word-list of COVID-19 pandemic language classified as medical, economic, political, and psychosocial lexemes; (2) identify the word-formation processes operating on the COVID-19 related vocabulary, and (3) determine which words are prevalent and unique in L1, L2 Asian, and L2 African varieties of the English language based on their occurrences in the corpus. The study identified 590 pandemic-related words drawn from the News on the Web (NOW) corpus dating from January 2020 to October 2021. The psychosocial category of the pandemic lexicon constitutes the biggest category of words identified from the corpus. The word-formation processes that operated in the production of the pandemic lexemes are compounds, blends, affixation, acronyms, and back-formation. L1 countries have the highest number of pandemic neologisms, prevalent or high-frequent pandemic lexemes, and unique word combinations. People produce neologisms as a coping mechanism to overcome various stressors and reflect their pandemic-related experiences.